Is There a Relationship Between Maxillary Sinus’s Inferior Pneumatisation and Sinonasal Variations? A Retrospective CBCT Study - Sevde Göksel; Arif Yiğit Güler (eJournal of Oral Maxillofacial Research)
Objectives: This retrospective study aims to analyse alveolar and palatal process pneumatisation and their relationships with sinonasal variations using cone-beam computed tomography.